Serial Intrauterine Transfusions for a Hydropic Fetus with Severe Anemia and Thrombocytopenia Caused by Parvovirus: Lessons Learned - Argoti, Pedro S.; Bebbington, Michael; Adler, Michael; Johnson, Anthony; Moise, Kenneth J., Jr. (American Journal of Perinatology Reports, 2013)
Introduction Fetal exsanguination is a rare complication of cordocentesis. Successful correction of fetal thrombocytopenia is essential for the reduction of risks.Case Report A 25-year-old, gravida 3, P2-0-0-0-2, was referred at 27 weeks of gestation for evaluation of newly diagnosed nonimmune hydrops secondary to parvovirus infection. Despite the use of ancillary platelet transfusions to correct the severe fetal thrombocytopenia, prolonged bleeding from the cord puncture site still occurred, necessitating five intrauterine transfusions to ultimately correct the fetal anemia.Conclusions The use of a smaller-diameter procedure needle, correction of the fetal thrombocytopenia early in the procedure, and external cord compression with the ultrasound transducer were ultimately successful measures in allowing for minimal loss of transfused red cells from the intravascular compartment.
Keywords: parvovirus; intrauterine transfusion; fetal thrombocytopenia; platelet count